Active PinScreen: Exploring Spatio-Temporal Tactile Feedbackfor Multi-Finger Interaction - Chi Zhang (22nd International Conference on Human-Computer Interaction with Mobile Devices and Services, 2020)
Multiple fingers are often used for efficient interaction with handheld computing devices. Currently, any tactile feedback provided is felt on the finger pad or the palm with coarse granularity. In contrast, we present a new tactile feedback technique, Active PinScreen, that applies localised stimuli on multiple fingers with fine spatial and temporal resolution. The tactile screen uses an array of solenoid-actuated magnetic pins with millimetre scale form-factor which could be deployed for back-of-device handheld use without instrumenting the user. As well as presenting a detailed description of the prototype, we provide the potential design configurations and the applications of the Active PinScreen and evaluate the human factors of tactile interaction with multiple fingers in a controlled user evaluation. The results of our study show a high recognition rate for directional and patterned stimulation across different grip orientations as well as within- and between- fingers. We end the paper with a discussion of our main findings, limitations in the current design and directions for future work.